PARENTAL HABITUATION METHODS IN RELATION TO EARLY CHILDHOOD LEARNING AUTONOMY: A CASE STUDY IN BAJAWA DISTRICT EAST OF NUSA TENGGARA - Meo, Lidia; Laksana, Dek Ngurah Laba; Ngura, Elisabeth Tantiana; Oka, Gde Putu Arya (STKIP Citra Bakti, 2026)
This study is grounded in the importance of learning independence as a foundation for young children’s academic readiness and self-regulation; however, its implementation at home is often shaped by variations in parental habituation practices and family constraints. The study aims to describe parents’ habituation methods in educating children, identify habituation practices used to foster children’s learning independence, and map the constraints faced by parents in Bajawa District. A qualitative approach with a case study design was employed. Data were collected through interviews with parents and teachers and observations of children during learning activities, then analyzed thematically and validated through source and method triangulation. The findings indicate that parental habituation is reflected in adaptive learning schedules, routines of preparing and tidying learning materials, the provision of simple tasks accompanied by opportunities for children to take initiative, and appreciation for independent efforts. In school, learning independence is indicated by initiative to start activities, responsibility, discipline, self-confidence, and problem-solving ability. Variation emerged in step-by-step assistance because some parents tended to take over tasks, reducing children’s opportunities to practice. Major constraints included limited time due to work, a less conducive home learning environment, fluctuating moods, and low attention during learning. These findings highlight the need for consistent yet flexible habituation, improved quality of step-by-step guidance, and strengthened home–school collaboration to support children’s learning independence